Achieving ultrahigh triboelectric charge density for efficient energy harvesting - Wang, Jie; Wu, Changsheng; Dai, Yejing; Zhao, Zhihao; Wang, Aurelia; Zhang, Tiejun; Wang, Zhong Lin (Nature communications, 2017)
With its light weight, low cost and high efficiency even at low operation frequency, the triboelectric nanogenerator is considered a potential solution for self-powered sensor networks and large-scale renewable blue energy. As an energy harvester, its output power density and efficiency are dictated by the triboelectric charge density. Here we report a method for increasing the triboelectric charge density by coupling surface polarization from triboelectrification and hysteretic dielectric polarization from ferroelectric material in vacuum ( P ~ 10 −6 torr). Without the constraint of air breakdown, a triboelectric charge density of 1003 µC m −2 , which is close to the limit of dielectric breakdown, is attained. Our findings establish an optimization methodology for triboelectric nanogenerators and enable their more promising usage in applications ranging from powering electronic devices to harvesting large-scale blue energy. Triboelectric nanogenerators (TENGs) harvest ambient mechanical energy and convert it into electrical energy. Here, the authors couple surface polarization from contact electrification with dielectric polarization from a ferroelectric material in vacuum to dramatically enhance the TENG output power.